A new zero-voltage transition pulse width modulated boost converter - Bodur, H.; Cetin, S.; Yanik, G. (INST ENGINEERING TECHNOLOGY-IET, 2011)
In this study, a new active snubber cell is proposed for pulse width modulated (PWM) converters. This snubber cell provides zero-voltage transition (ZVT) turn on and zero-voltage switching (ZVS) turn off for the main switch. In the converter with the new snubber cell, auxiliary switch is turned on with zero current switching and turned off with ZVS. Also, the main diode and all of auxiliary diodes are operating with soft switching (SS). At the same time, in this converter, all SS energy stored in the snubber inductance is transferred effectively to the output by a transformer, and so the current stress of the auxiliary switch is reduced significantly. Also, this transformer provides possibility of using the capacitors required for ZVS turning off of the main and auxiliary switches. In this converter, no semiconductor device has any additional voltage and current stresses and SS-operating conditions are maintained at very wide line and load ranges. In this study, detailed steady state analysis of the new ZVT-PWM boost converter is presented, and this theoretical analysis is verified experimentally by a 1 kW and 100 kHz prototype.
Keywords: PWM CONVERTERS; Engineering